A web tool-based equal gender pay analysis for a competitive Europe (equal pacE): Overview, elements and lessons learned - Andrea Hammermann; Jörg Schmidt; Oliver Stettes; Frank Behrmann; Felicia Lonnes; Caroline Merk (Institut der deutschen Wirtschaft (IW), 2016)
The project equal pacE aimed to provide and promote a web tool by which companies can voluntarily analyse their pay structures and detect a potentially existing gender pay gap and its causes. The equal pacE web tool has been made available in five languages: Dutch, English, Finnish, French, and Polish. Its use is free of charge. The equal pacE web tool is based on the well-established web tool Logib-D that has been funded by the German Federal Ministry for Family Affairs, Senior Citizens, Women and Youth. It was adjusted for the country-specific requirements in Flemish-Belgium and the Netherlands, as well as in Finland, France, Poland, and the United Kingdom.
Keywords: C20; J31; O15; 330